Collecting and Analyzing IBD Clinical Data for Machine-Learning: Insights from an Italian Cohort - Aldo Marzullo; Victor Savevski; Maddalena Menini; Alessandro Schilirò; Gianluca Franchellucci; Arianna Dal Buono; Cristina Bezzio; Roberto Gabbiadini; Cesare Hassan; Alessandro Repici; Alessandro Armuzzi (Data, 2025)
Research of Inflammatory Bowel Disease (IBD) involves integrating diverse and heterogeneous data sources, from clinical records to imaging and laboratory results, which presents significant challenges in data harmonization and exploration. These challenges are also reflected in the development of machine-learning applications, where inconsistencies in data quality, missing information, and variability in data formats can adversely affect the performance and generalizability of models. In this study, we describe the collection and curation of a comprehensive dataset focused on IBD. In addition, we present a dedicated research platform. We focus on ethical standards, data protection, and seamless integration of different data types. We also discuss the challenges encountered, as well as the insights gained during its implementation.